Improved cardiac and venous pressures during hospital stay in patients with acute heart failure: an echocardiography and biomarkers study. (11th April 2020) - Akiyama, Eiichi; Cinotti, Raphaël; Čerlinskaitė, Kamilė; Van Aelst, Lucas N.L.; Arrigo, Mattia; Placido, Rui; Chouihed, Tahar; Girerd, Nicolas; Zannad, Faiez; Rossignol, Patrick; Badoz, Marc; Launay, Jean‐Marie; et al.
Abstract: Aims: Changes in echocardiographic parameters and biomarkers of cardiac and venous pressures or estimated plasma volume during hospitalization associated with decongestive treatments in acute heart failure (AHF) patients with either preserved left ventricular ejection fraction (LVEF) (HFPEF) or reduced LVEF (HFREF) are poorly assessed. Methods and results: From the metabolic road to diastolic heart failure: diastolic heart failure (MEDIA‐DHF) study, 111 patients were included in this substudy: 77 AHF (43 HFPEF and 34 HFREF) and 34 non‐cardiac dyspnea patients. Echocardiographic measurements and blood samples were obtained within 4 h of presentation at the emergency department and before hospital discharge. In AHF patients, echocardiographic indices of cardiac and venous pressures, including inferior vena cava diameter [from 22 (16–24) mm to 13 (11–18) mm, P = 0.009], its respiratory variability [from 32 (8–44) % to 43 (29–70) %, P = 0.04], medial E/e' [from 21.1 (15.8–29.6) to 16.6 (11.7–24.3), P = 0.004], and E wave deceleration time [from 129 (105–156) ms to 166 (128–203) ms, P = 0.003], improved during hospitalization, similarly in HFPEF and HFREF patients. By contrast, no changes were seen in non‐cardiac dyspnea patients. In AHF patients, all plasma biomarkers of cardiac and venous pressures, namely B‐type natriuretic peptide [from 935 (514–2037) pg/mL to 308 (183–609) pg/mL, P < 0.001], mid‐regional pro‐atrial natriuretic peptide [from 449 (274–653) pmol/L to 366 (242–549) pmol/L, P < 0.001], and soluble CD‐146 levels [from 528 (406–654) ng/mL to 450 (374–529) ng/mL, P = 0.003], significantly decreased during hospitalization, similarly in HFPEF and HFREF patients. Echocardiographic parameters of cardiac chamber dimensions [left ventricular end‐diastolic volume: from 120 (76–140) mL to 118 (95–176) mL, P = 0.23] and cardiac index [from 2.1 (1.6–2.6) mL/min/m 2 to 1.9 (1.4–2.4) mL/min/m 2, P = 0.55] were unchanged in AHF patients, except tricuspid annular plane systolic excursion (TAPSE) that improved during hospitalization [from 16 (15–19) mm to 19 (17–21) mm, P = 0.04]. Estimated plasma volume increased in both AHF [from 4.8 (4.2–5.6) to 5.1 (4.4–5.8), P = 0.03] and non‐cardiac dyspnea patients ( P = 0.01). Serum creatinine [from 1.18 (0.90–1.53) to 1.19 (0.86–1.70) mg/dL, P = 0.89] and creatinine‐based estimated glomerular filtration rate [from 59 (40–75) mL/min/1.73m 2 to 56 (38–73) mL/min/1.73m 2, P = 0.09] were similar, while plasma cystatin C [from 1.50 (1.20–2.27) mg/L to 1.78 (1.33–2.59) mg/L, P < 0.001] and neutrophil gelatinase associated lipocalin (NGAL) [from 127 (95–260) ng/mL to 167 (104–263) ng/mL, P = 0.004] increased during hospitalization in AHF. Conclusions: Echocardiographic parameters and plasma biomarkers of cardiac and venous pressures improved during AHF hospitalization in both acute HFPEF and HFREF patients, while cardiac chamber dimensions, cardiac output, and estimated plasma volume showed minimal changes.